BEING A CHURCH IN A SECULARISED WORLD: TAKING OFF FROM VATICAN II - Mascarenhas, Theodore (Asian Horizons, 2013)
The Council focuses its attention on the world of men, the whole human family along with the sum of those realities in the midst of which it lives; that world which is the theater of man’s history, and the heir of his energies, his tragedies and his triumphs; that world which the Christian sees as created and sustained by its Maker’s love…1 With these words the Second Vatican Council announced to the world, the active participatory role of the Church. The Council Fathers intended to make it clear that the realm of faith and the so called “secular” world could not be treated as two separate irreconcilable entities but as a single integrated reality. And in another document the Council Fathers once again indicated the whole hearted involvement of the Church in the affairs of the World. In Lumen Gentium, the Council Fathers wrote, “The present-day conditions of the world add greater urgency to this work of the Church so that all men, joined more closely today by various social, technical and cultural ties, might also attain fuller unity in Christ.”